1988
DOI: 10.1080/00365599.1988.11690413
|View full text |Cite
|
Sign up to set email alerts
|

Comparison Between Renal Parenchymal Sonographic Volume, Renal Parenchymal Urographic Area, Glomerular Filtration Rate and Renal Plasma Flow in Children

Abstract: A comparison of renal size, expressed as ultrasonographic renal parenchymal volume and urographic renal parenchymal area, and renal function, measured as glomerular filtration rate (GFR) and effective renal plasma flow (ERPF), was made in two groups of children: (1) 21 patients with normal urograms and no signs of current disease and (2) 26 children with recurrent urinary tract infections or asymptomatic bacteriuria. Renal parenchymal volume was calculated using a water delay ultrasonographic device (Octoson).… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
17
0
1

Year Published

1994
1994
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 14 publications
1
17
0
1
Order By: Relevance
“…This may be due to a relatively low number of infants in the partially breast and fully formula-fed groups or the uncertainty of the method of clearance estimation. Other studies have shown that GFR is positively associated with kidney size [31,32,33,34], and both increased GFR and kidney size have been found in young rats on a high-protein diet [1].…”
Section: Discussionmentioning
confidence: 92%
“…This may be due to a relatively low number of infants in the partially breast and fully formula-fed groups or the uncertainty of the method of clearance estimation. Other studies have shown that GFR is positively associated with kidney size [31,32,33,34], and both increased GFR and kidney size have been found in young rats on a high-protein diet [1].…”
Section: Discussionmentioning
confidence: 92%
“…Upon the analysis of study results, all analyzed parameters of kidney dimensions correlated significantly with parameters of kidney function. 3,4,19,21,22 When this group was divided to subgroups by sex, the threshold of significance of tested correlation was not always achieved, most probably due to small number of subjects. 9,20 Burkhardt et al studied correlation between kidney dimensions and function in elderly and found the best correlation between the kidney parenchyma volume and creatinine clearance.…”
Section: Discussionmentioning
confidence: 99%
“…The correlation between kidney size and renal function has not been carefully examined. Several studies have shown a good correlation between GFR and renal size measured urographically or sonographically in children (42)(43)(44)(45). Correlations between size and function have been found in adults with hypertension or renal disease using urography (46), in diabetics (1,38) and elderly hospitalized patients (47) using sonography, and in disease-free cancer patients using CT scanning (23).…”
Section: Discussionmentioning
confidence: 99%